Transmission of Business Cycle Shocks between Unequal Neighbours: Germany and Austria - Gerhard Fenz; Martin Schneider (Oesterreichische Nationalbank (OeNB), 2007)
This paper analyses the comovement of the German and Austrian economies and the transmission of German shocks to Austria. Static and dynamic correlation measures show a strong comovement and a change of the relative position in time of these two economies. The transmission of German shocks to Austria is analysed with a two-country VAR model. Using sign restrictions on impulse response functions, we identify German supply, demand and monetary policy shocks. We find that the average reaction of the Austrian economy to German shocks amounts to 44% of the German reaction and remains broadly stable over time.
Keywords: C32; E32; F41; 330; business cycle; synchronization; vector autoregression; shock transmission; Austria; Germany